(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Stylistic awareness of the discoursal properties of Pus is also important in such pragmatic areas as compilation of dictionaries and glossaries, as well as making notes and comments on literary texts. It is of crucial importance to reassess this area of applied stylistics in the light of a discourse-based stylistic approach to language. First I would like to explore a number of challenges in lexicography caused by instantial use